Three-dimensional non-planar crack growth analysis using enriched finite elements. (1st April 2022) - Kurt, Emre; Demir, Oğuzhan; Ayhan, Ali O.
Abstract: The paper presents computational mixed mode non-planar fatigue crack growth analyses using F racture and C rack P ropagation A nalysis S ystem (FCPAS), which employs enriched crack tip finite elements to calculate the mixed mode stress intensity factors (SIFs) and utilizes from other sub-modules to predict the evolving crack growth trajectories and the resulting fatigue crack growth lives. Numerical applications on different problems selected from the literature; a hollow shaft, an H-shaped specimen and cylindrical rods containing cracks with different initial orientations and sizes and subjected to different fatigue loading types are presented. Comparisons of results from the numerical analyses with the corresponding data from the literature agree well in terms of computed SIFs, predicted evolving crack paths and crack propagation lives.